Realizing good combinations of strength-ductility and corrosion resistance in a Co-free Fe4Ni4Mn2CrTi high-entropy alloy via tailoring Ni/Ti-rich precipitates and heterogeneous structure - Chu, Chenliang; Chen, Weiping; Fu, Zhiqiang; Huang, Liran; Wang, Hao; Zhu, Dezhi (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2023)
The development of alloys with good combinations of strength-ductility and corrosion resistance is a long-standing research theme for advanced materials engineering, which also holds true for the newly emerged high-entropy alloys (HEAs). Here, Ni/Ti-rich precipitates and heterogeneous structure were introduced for the primary purpose of improving strength-plasticity synergy of a Co-free Fe4Ni4Mn2CrTi HEA with good anti-corrosion performance. Specifically, four typical states of this HEA were tailored and compared, including i) as-cast, ii) homogenized, iii) post deformation annealing (PDA) sample with heterogeneous structure and iv) PDA sample with homogeneous structure. The structural features, mechanical properties, and underlying phase transformation mechanisms were systematically investigated. Phase transformation of η-D024 to γ′-L12 was realized during annealing treatments, based on the intrinsic stacking faults formed by repeating removal of the (0001) planes in the η structure. Compared with the homogenized counterpart, the strength-ductility synergy was achieved in the alloy iv, showing an evident increment of ∼43.4% in yield strength (σ0.2) and ∼57.8% in ultimate tensile strength (σUTS), respectively, resulting from solid-solution strengthening, grain-boundary strengthening and precipitation strengthening, yet without sacrificing ductility. Good combinations of strength and ductility were also achieved in the alloy iii with heterogeneous structure, possessing an even higher σ0.2 and σUTS yet maintaining a moderate elongation, whose strength contribution from hetero-deformation induced hardening is recognized as a significant strengthening mechanism. Additionally, in comparison with the conventional corrosion-resistant 304 stainless steel, compact TiO2 and Cr2O3 in the passive film give rise to more superior anti-corrosion properties of the homogenized HEA. This paper provides a new paradigm in the controllable design of novel low-cost high-performance HEAs for achieving their potential structural and functional engineering applications.